2014
DOI: 10.1021/nl504042u
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Dependence of Hydrogen Oxidation Kinetics on the Size of Pt Nanoparticles by in Operando Nanoplasmonic Temperature Sensing

Abstract: We use a noninvasive nanoscale optical-temperature measurement method based on localized surface plasmon resonance to investigate the particle size-dependence of the hydrogen oxidation reaction kinetics on model supported Pt nanocatalysts at atmospheric pressure in operando. With decreasing average nanoparticle size from 11 down to 3 nm, the apparent reaction activation energy is found to increase from 0.5 up to 0.8 eV. This effect is attributed to an increase of the fraction of (100)-facet and edge and corner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…In Figure 3b−f, we plot the measured change in the plasmon peak position, Δλ peak , of flat sensors coated with homogeneous PMMA films (thickness range from 21 to 370 nm), as a function of temperature. At this point it is important to note that the observed peak shifts are calibrated such that the contribution from the intrinsic thermal sensitivity 33 of the plasmonic elements used is removed by subtraction of a blank sensor reference measurement (see Figure S4 for details). Thus, the response is solely due to the thermal evolution of the PMMA films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In Figure 3b−f, we plot the measured change in the plasmon peak position, Δλ peak , of flat sensors coated with homogeneous PMMA films (thickness range from 21 to 370 nm), as a function of temperature. At this point it is important to note that the observed peak shifts are calibrated such that the contribution from the intrinsic thermal sensitivity 33 of the plasmonic elements used is removed by subtraction of a blank sensor reference measurement (see Figure S4 for details). Thus, the response is solely due to the thermal evolution of the PMMA films.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Such experiments have not yet been attempted although there are a few LSPR reports describing the effect of temperature on glucose detection in serum samples, 28 the optical response of polymer-functionalized gold nanoprisms, 29 vesicle adsorption and deformation, 30 and heterogeneous catalytic reactions. 31 Herein, the main objective was to investigate the temperature-dependent adsorption of bovine serum albumin (BSA) protein onto silica-coated gold nanodisk arrays by indirect nanoplasmonic sensing measurements, thereby establishing an analytical framework to interpret LSPR measurement data collected in protein adsorption studies. BSA is a 66 kDa protein that was selected for the experimental work because it is widely studied as a model of serum albumins and utilized in various biochemical applications.…”
mentioning
confidence: 99%
“…The latter feature would be particularly advantageous for monitoring protein adsorption at different temperatures. Such experiments have not yet been attempted although there are a few LSPR reports describing the effect of temperature on glucose detection in serum samples, the optical response of polymer-functionalized gold nanoprisms, vesicle adsorption and deformation, and heterogeneous catalytic reactions …”
mentioning
confidence: 99%
“…[4][5][6][7][8] The concentration of edge, corner, and facet sites, which are a function of particle size, has been found to have a profound effect on the particle's catalytic activity. [9][10][11][12] It has been observed that the spatial variation of elements in bimetallic systems affects the nanoparticle's catalytic properties by controlling the surface strain and in-situ etching. [13][14][15] Recent studies with bimetallic nanoparticle systems have shown that the elemental distribution within the alloys is not homogenously distributed.…”
mentioning
confidence: 99%